2010
DOI: 10.1002/jcp.22049
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin suppresses HeLa cell viability via AMPK‐induced HSP70 and EGFR down‐regulation

Abstract: Quercetin, an anti-oxidant flavonoid that is widely distributed in the plant kingdom, has been suggested to have chemopreventive effects on cancer cells, although the mechanism is not completely understood. In this study, we found that quercetin increased the phosphorylation of AMP-activated protein kinase (AMPK) and downstream acetyl-CoA carboxylase (ACC) and suppressed the viability of HeLa cells. AICAR, an AMPK activator, and quercetin down-regulated heat shock protein (HSP)70 and increased the activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 49 publications
4
46
0
1
Order By: Relevance
“…Data were analyzed by Student's t-test [3]. A possibility exist that quercetin might have induced oocyte apoptosis in NLE-treated animals possibly through the generation of ROS as has been reported for various somatic cell types [4,11,23,24]. This possibility is further strengthened by the data of present study that in vivo NLE treatment significantly increased H 2 O 2 and total nitrite concentrations and thereby morphological apoptotic features in oocytes.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Data were analyzed by Student's t-test [3]. A possibility exist that quercetin might have induced oocyte apoptosis in NLE-treated animals possibly through the generation of ROS as has been reported for various somatic cell types [4,11,23,24]. This possibility is further strengthened by the data of present study that in vivo NLE treatment significantly increased H 2 O 2 and total nitrite concentrations and thereby morphological apoptotic features in oocytes.…”
Section: Discussionsupporting
confidence: 53%
“…This notion is further supported by our data that NLE treatment significantly increased cytochrome c concentration in oocyte that had morphological apoptotic features. Although NLE-induced generation of ROS and cytochrome c release in oocyte have not been reported till date, quercetin-induced generation of ROS and cytochrome c release from mitochondria has been reported in various somatic cell types [23,24,30]. Taken together, these findings suggest that NLE-induced generation of ROS trigger cytochrome c release from mitochondria that may initiate apoptotic signals in oocytes.…”
Section: Discussionmentioning
confidence: 82%
“…In previous studies quercetin was implied as an apoptotic activator and antioxidant as well as protective agent against various types of cancer (Jung et al, 2010). It was shown that quercetin can inhibit proliferation of tumor cells and reduce the number of aberrant crypt foci in colon tumors (Van Erk et al, 2005) that it can facilitate programmed cell death in lung carcinoma (Nguyen et al, 2004) and colonorectal tumor cells (Richter et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the lack of evidence on AMPK downstream targets, it remains unclear how AMPK activation influences CAR nuclear translocation. Pharmacological activation of AMPK seems to down-regulate HSP70 and EGFR and activate PP2A, suggesting that AMPK may trigger CAR nuclear translocation through the regulation of suppressive proteins [33][34][35] . In addition, how some of the coactivators drive ligand-independent nuclear translocation of CAR in vivo is still unclear.…”
Section: Nuclear Translocation Of Carmentioning
confidence: 99%